Relationship of TPACK, motivation, self-regulation, and learning performance on preservice primary school teachers - Thohir, M. Anas; Yanti, Fitri April; Handayani, Rif’ati Dina; Halim, Lilia (Institute of Advanced Engineering and Science, 2025)
Technological development could enable pre-service teachers to adopt web design with strong pedagogy, however adaptation requires still unclear an explicit exploration of the factors. This study aimed to identify the effect of technological pedagogical content knowledge (TPACK) on motivation, self-regulation, and learning achievement. It surveyed 406 pre-service teachers from 12 higher education institutions in Indonesia. Data validity and reliability were checked using an exploratory factor, confirmatory, and part analyses. The partial least squares structural equation modelling (PLS-SEM) results showed that TPACK has the most significant role in learning motivation. The result shows that technology integration knowledge also significantly affects self-regulated learning (SRL). In addition, pre-service teachers’ TPACK supports their learning motivation to use the web, as well as their academic achievement. Moreover, most students’ achievements were constructed by TPACK, learning motivation, and self-regulation. This study implies that the instructor should clarify the project mission and the inquiry system activities in the educational technology course.